2002
DOI: 10.1200/jco.2002.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Prostate-Specific Antigen–Activated Peptide-Doxorubicin Conjugate in Patients With Prostate Cancer

Abstract: This is the first study of selective drug delivery in humans using a novel PSA-activated agent. L-377202 was cleaved to produce detectable levels of the active metabolites Leu-Dox and Dox. L-377202 was well tolerated and established a safe dose level for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 10 publications
0
42
0
Order By: Relevance
“…The first human trial with L-377,202 were recently completed and suggest that some of the improvements observed in mice will be translated to humans (42). In the case of MMP-activated prodrugs, this issue is particularly difficult to address because mouse tumors are poor models for human tumors with respect to MMP expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…The first human trial with L-377,202 were recently completed and suggest that some of the improvements observed in mice will be translated to humans (42). In the case of MMP-activated prodrugs, this issue is particularly difficult to address because mouse tumors are poor models for human tumors with respect to MMP expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…These include proteins containing anthrax toxin fused to sequences cleaved specifically by uPA [123] or an-thracycline non-toxic pro-drugs that can be converted to an active parent drug by uPA [123], plasmin [124], or other serine proteinase such as prostate-specific antigen [125,126].…”
Section: Exploitation Of Proteolytic Activitymentioning
confidence: 99%
“…At the recommended dose of 225 mg/m 2 , equivalent to 90 mg of DOX/m 2 on a molar basis, two patients had a greater than 75% decline in PSA. A preferential delivery of DOX to PSA-positive tumor cells was not measured, but toxicity data indicated that it was possible to safely deliver about 1.5-fold more anthracycline compared with the conventional formulation on a molar basis (DiPaola et al, 2002).…”
mentioning
confidence: 99%